Evaluation of testicular blood flow during testicular torsion surgery in children using the indocyanine green–guided near-infrared fluorescence imaging technique - Liu, Xiaomeng; Xu, Yi; Li, Long; Bai, Dongsheng (Frontiers in Pediatrics, 2023)
Objective: To investigate the feasibility of indocyanine green-guided near infrared fluorescence (ICG-NIRF) imaging technique in evaluating testicular blood flow during testicular torsion (TT) surgery in pediatric cases.We retrospectively analyzed the 8 pediatric cases with TT who underwent surgery in our hospital from February to July 2023. The intraoperative two-step method of ICG-NIRF imaging and testicular incision was used to evaluate the testicular blood flow, followed by a selection of different surgical methods. The removed testes were pathologically examined after surgery, and all patients were followed-up one month after surgery for evaluation of testicular blood flow using gray-scale ultrasound and Color Doppler flow imaging (CDFI).Results: 8 pediatric TT patients were enrolled, aged from 1 to 16 years, with a median age of 11.5 years. The time from the onset ranged from 4 to 72 hours (mean 26.13±25.09 hours). A total of 8 testes were twisted, including 4 on the left side and 4 on the right side. The twisting direction of testes was clockwise in 4 cases and counterclockwise in 4 cases. Rotation of torsion was 180° to 1080° (mean 472.5°±396°). There was no statistically significant difference in imaging time between the 4 patients with testicular blood vessels imaging on both the torsional and normal sides (P > 0.05). The postoperative recovery was uneventful with no complications occurred during the follow-up period of one month. The postoperative histopathological results of 3 patients who underwent orchiectomy showed extensive hemorrhage, degeneration and necrosis of testicular tissue. Among the 5 patients who underwent orchiopexy, gray-scale ultrasound and CDFI examinations at one month after surgery showed that the uniform internal echo of testes and the normal blood flow signals in 4 patients. One patient with no testicular blood vessels imaging on the torsional side showed uneven internal echo of the testis and no blood flow signals.This is a provisional file, not the final typeset article Conclusion: ICG-NIRF imaging is a feasible method to evaluate testicular blood flow during TT surgery. Testicular blood vessels imaging within five minutes after ICG injection might be the basis for testicular retention during TT surgery.